Strategi pemasaran untuk meningkatkan penjualan rol film lokal di Tomo Film - Rafael Pandu Christo; Hadisantono; Lenny Halim (Jurnal Teknik Industri dan Manajemen Rekayasa, 2024)
Tomo Film is a company in Yogyakarta that sells all kinds of necessities for analog photography, especially roll-film. The roll-film procurement system at Tomo Film came from 2 sources, namely import and local. The main source was from imported film rolls. However, bringing in imported roll- film to meet consumer needs can only be done in 1st and 3rd quarters. This issue caused the sales volume being fluctuate in each quarter. The aim of this research was to improve marketing strategies to increase sales of local film rolls. By using Product Life Cycle calculations it was found that this company was in the decline stage. Furthermore, using the AHP method, priority solutions to problems were obtained. The chosen marketing strategy was a Pop Up Store with an excess stock of local roll-film based on questionnaires which were distributed to 100 respondents who were members of the Yogyakarta Analog Camera Community (ANALOG). The results of the implementation in the form of a Pop Up Store which was carried out for 2 days, demonstrated that sales of local roll-film increased by 39 pieces (32.42%).